Perspektif Hukum terhadap Tindak Pidana Perdagangan Orang di Kawasan ASEAN antara Indonesia dan Myanmar - Mugiono , Mariana; Indradewi, Astrid Athina; Achmad , Andyna Susiawati (Journal of Contemporary Law Studies, 2024)
This research is to address human trafficking in Myanmar is a deeply councerning issue. The situation is exacerbated by the ongoing conflict and the lack of effective governance in many areas. Human trafficking is a serious transnational crime threatening global security, particularly in Southeast Asia. Economic factors like poverty and job scarcity make many individuals vulnerable to exploitation. Indonesia, as a major labor supplier, often serves as a source, transit, and destination for human trafficking. ASEAN has implemented measures like the ASEAN Plan of Action Against Trafficking in Persons, but challenges remain due to legal disparities among member states. Indonesia's laws, including the Anti-Trafficking Law, provide a framework to combat this crime, yet improvements in enforcement and victim support are needed. This is a dogmatic normative juridical method, which involves exploration, examines, and explanation of legal doctrines and rules to address the legal issues.T he research concludes that regional and international cooperation is vital, including information sharing and law enforcement collaboration. ASEAN should consider revising the principle of non-intervention and establishing a regional human rights court. Firm actions, such as economic sanctions, may be needed against those involved in trafficking, including Myanmar's military junta. Effective law enforcement and cooperation are essential for ASEAN members to collectively address human trafficking, ensuring security and legal certainty for all.